2017
DOI: 10.1111/bcp.13445
|View full text |Cite
|
Sign up to set email alerts
|

Is acetaminophen associated with a risk of Stevens–Johnson syndrome and toxic epidermal necrolysis? Analysis of the French Pharmacovigilance Database

Abstract: After analysis of the French pharmacovigilance data using the ALDEN algorithm, we found no obvious SJS/TEN risk related to the use of acetaminophen in this large national series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
(62 reference statements)
0
20
0
4
Order By: Relevance
“…epidermal necrolysis) was manually written in the certificate of death by the practitioner in charge of the patient, so the diagnosis is probably more reliable. Likewise, false‐positive cases in the FPVD and RegiSCAR databases are estimated to be low . Secondly, the capture–recapture method has other limitations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epidermal necrolysis) was manually written in the certificate of death by the practitioner in charge of the patient, so the diagnosis is probably more reliable. Likewise, false‐positive cases in the FPVD and RegiSCAR databases are estimated to be low . Secondly, the capture–recapture method has other limitations .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, false-positive cases in the FPVD and RegiSCAR databases are estimated to be low. 25 Secondly, the capture-recapture method has other limitations. [15][16][17] The possible dependence between sources was controlled by including interaction terms into the models, but this might not be adaptable to small capture samples and may have led to a lack of precision in the estimated interaction coefficient and in turn may have affected the estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding the association between medications treated for a dental diseases and SJS are scarce. 10,16,17 Owing to the presence of a mild cutaneous lesion, the patient in this study was diagnosed with atypical SJS, according to the study by Lebrun-Vignes et al 4…”
Section: Discussionmentioning
confidence: 99%
“…2 The difference between SJS, SJS/TEN overlap, and TEN is defined by the percentage of epidermal detachment with respect to body surface area distinguishes: SJS is defined as skin involvement of <10%; TEN is defined as skin involvement of >30%; and SJS/TEN overlap as 10%-30% skin involvement, resulting in increasing severity and a worsening prognosis of the disease as the percentage of skin involvement increases. 3,4 Drugs, such as anti-epileptic drugs, antibiotics, pain killers/antipyretics, and/or bacterial infections, such as Mycoplasma pneumoniae, and viral, such as herpes virus infections have been widely known to cause SJS. 2,[5][6][7][8] Till date, many marketed drugs are known to cause SJS.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, as the use of amoxicillin has been associated with SJS , the use of this product may be a confounding factor in the analysis of the causal relationship between calcium carbimide and SJS. In relation to paracetamol, on the other hand, one recently-published study by Lebrun-Vignes (2017) suggested that there is no evidence for a causal relationship between the use of paracetamol and the occurrence of SJS and TEN.…”
Section: Discussionmentioning
confidence: 99%